NEUROPROTECTIVE EFFECT OF TERMINALIA CHEBULA EXTRACTS AND ELLAGIC ACID IN PC12 CELLS - Shen, Yuh-Chiang; Juan, Chi-Wen Juan; Juan, Chi-Wen Juan; Lin, Che-San; Lin, Che-San; Chen, Chien-Chih; Chen, Chien-Chih; Chang, Chia-Lin; Chang, Chia-Lin (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Alzheimer’s disease (AD) is one of the most prevalent severe neurological disorders afflicting our aged population. The study was to determine neuroprotective effects of the Terminalia chebula extracts and ellagic acid by using beta-amyloid25-35 (Ab25-35)-induced cell cytotoxicity in undifferentiated rat pheochromocytoma (PC12) cellular model. The methanolic and water extracts of T. chebula and ellagic acid exhibited the strongest neuroprotective activity against Ab25-35-induced undifferentiated PC12 cell deaths at 0.5–5.0 ug/ml. The ellagic acid also exhibited the partial neuroprotective activity against H2O2-induced undifferentiated PC12 cell deaths at 0.5–5.0 ug/ml. The methanolic and water extracts of T. chebula and ellagic acid protected undifferentiated PC12 cells from the damaging effects of Ab25-35 in several ways: (1) by securing cell viability; (2) by suppressing reactive oxygen species production; and (3) by eliminating calcium ion influx. The T. chebula extracts maybe represent a promising plant-source for medicine in the application of the treatment of AD. Further investigation of the ellagic acid is necessary to verify the neuroprotective efficacy and mechanisms in vivo.